2007
DOI: 10.1186/1471-2180-7-91
|View full text |Cite
|
Sign up to set email alerts
|

IS1111 insertion sequences of Coxiella burnetii: characterization and use for repetitive element PCR-based differentiation of Coxiella burnetii isolates

Abstract: Background: Coxiella burnetii contains the IS1111 transposase which is present 20 times in the Nine Mile phase I (9Mi/I) genome. A single PCR primer that binds to each IS element, and primers specific to a region ~500-bp upstream of each of the 20 IS1111 elements were designed. The amplified products were characterized and used to develop a repetitive element PCR genotyping method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 18 publications
0
44
0
1
Order By: Relevance
“…The majority of PCR assays for C. burnetii have targeted the insertion sequence element IS1111 (6)(7)(8)(9)(10). As a mobile genetic element, there is the potential for IS1111 to move from one organism type to another, theoretically resulting in loss of specificity (11).…”
mentioning
confidence: 99%
“…The majority of PCR assays for C. burnetii have targeted the insertion sequence element IS1111 (6)(7)(8)(9)(10). As a mobile genetic element, there is the potential for IS1111 to move from one organism type to another, theoretically resulting in loss of specificity (11).…”
mentioning
confidence: 99%
“…Alternatively IS1111 transposons could be present but with highly variable sequences. Denison et al (2007) reported some sequence variability and deletions in individual copies of the IS1111 transposon of C. burnetii. Based on the data by Denison et al (2007) and GenBank sequences the primers described by Willems et al (1994) should amplify at least one copy of the IS1111 transposon in all C. burnetii isolates.…”
Section: Resultsmentioning
confidence: 99%
“…The three other isolates used in this study were from acute cases of Q fever in Australia and were classified as group III (typing method from [10] (data not shown).…”
Section: Discussionmentioning
confidence: 99%